Comminuted distal humeral fracture treated using the Ilizarov technique in a patient with rheumatoid arthritis and osteoporosis. (April 2016) - Chida, Shuichi; Nozaka, Koji; Miyakoshi, Naohisa; Yamada, Shin; Miyamoto, Seiya; Nagasawa, Hiroyuki; Kijima, Hiroaki; Sugimura, Yusuke; Shimada, Yoichi
Abstract: The goal of treatment for distal humeral fractures in patients with rheumatoid arthritis (RA) is to obtain sufficient bone union and good elbow function. However, treating comminuted distal humeral fractures in patients with RA and osteoporosis is challenging. We present the case of a 58-year-old woman with RA and osteoporosis who suffered a comminuted distal humeral fracture and was successfully treated with the Ilizarov technique. The Ilizarov technique is minimally invasive compared with conventional open surgery, can obtain good stabilization, and allows earlier rehabilitation, even if the fractured bone is severely osteoporotic. The patient exhibited good elbow function and alignment at the final follow-up examination (18 postoperative months). To the best of our knowledge, the present case is the first in which a comminuted distal humeral fracture in a patient with RA and severe osteoporosis was successfully treated with an Ilizarov external fixator.